Circulating miR-21 as a prognostic and predictive biomarker in oral squamous cell carcinoma - Mahmood, Nosheen (Pak J Med Sci, 2019)
BACKGROUND & OBJECTIVE: The high-throughput analysis of circulating microRNAs (miRNAs) is an active area of biomarker research. The oral cancer remains a common cancer among Pakistani males that continues to present at an advance stage, thus exhibiting poor survival. MiRNA 21 (miR-21) is the most consistently over-expressed miRNA in different types of tumor tissues. However, information regarding expression of miR-21 in plasma remains to be resolved. Therefore, present study was designed to investigate if miR-21 was expressed in plasma of patients with oral cancer, and further explore its diagnostic and prognostic potential. METHODS: Present study was conducted at Ziauddin University and Karachi Institute of Radiotherapy and Nuclear Medicine (KIRAN). Histologically confirmed cases of oral squamous cell carcinoma were recruited from Oncology Department of Ziauddin Hospital between 2013 and 2017. Controls were carefully selected after considering age, gender and socioeconomic condition. MiRNA was extracted and immediately reverse transcribed to cDNA. MiR-21 expression was evaluated using probes specifically designed for Real time quantitative polymerase chain reaction. RESULTS: A significant over expression of miRNA 21 was observed in histologically confirmed cases as compared to controls. The increased expression of miRNA 21 was also reported to be associated with tumor size, metastasis and local invasion (p<0.05). CONCLUSION: The expression of circulating miR-21 in plasma samples of oral cancer patients makes it a promising diagnostic and prognostic marker.